2016
DOI: 10.1515/jem-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Testing Exogeneity of Multinomial Regressors in Count Data Models: Does Two-stage Residual Inclusion Work?

Abstract: We study a simple exogeneity test in count data models with possibly endogenous multinomial treatment. The test is based on Two Stage Residual Inclusion (2SRI). Results from a broad Monte Carlo study provide novel evidence on important features of this approach in nonlinear settings. We …nd di¤erences in the …nite sample performance of various likelihood-based tests under correct speci…cation and when the outcome equation is misspeci…ed due to neglected over-dispersion or nonlinearity. We compare alternative 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We applied a two-stage residual inclusion (2SRI) method, an established method for producing consistent estimators for nonlinear parametric models [30,31]. In the first stage, the provider-patient discussion was modeled as a function of the IV and the aforementioned covariates using a multinomial logistic regression.…”
Section: Instrumental Variable (Iv) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We applied a two-stage residual inclusion (2SRI) method, an established method for producing consistent estimators for nonlinear parametric models [30,31]. In the first stage, the provider-patient discussion was modeled as a function of the IV and the aforementioned covariates using a multinomial logistic regression.…”
Section: Instrumental Variable (Iv) Analysismentioning
confidence: 99%
“…In the second stage, the individual dichotomized outcome variable was predicted as a function of the exposure variable, all covariates, and the standardized residuals obtained from the first stage using a binomial logistic regression. The standard errors of two-stage estimators were calculated by implementing a bootstrap method with 500 repetitions [30,31].…”
Section: Instrumental Variable (Iv) Analysismentioning
confidence: 99%
“…Wooldridge [54] recommended includingξ u nonlinearily and/or interactions with X e , X o in (34) to improve the approximation. Furthermore, a simulation study on different 2SRI settings suggested standardizing the variance of the first stage residuals [56].…”
Section: A23 Instrumental Variables and Gamlssmentioning
confidence: 99%
“…The 2SRI method is applicable when there are regressors in a nonlinear model that are correlated with unobserved (latent) variables, and these unobservables also influence the outcome variable. In the context of linear models, instrumental variable (IV) methods represent the established solution to the problem of endogeneity of regressors (Geraci, Fabbri and Monfardini, 2012). For example, the conventional Two-Stage Least Squares (2SLS) method is based on the assumption that the regression relationship of the outcome variable on the treatment variable and the observable confounders is linear.…”
Section: Two-stage Residual Inclusion (2sri)mentioning
confidence: 99%